RNA N6-Methyladenosine Modifications and the Immune Response - Ya-Nan Wang; Chen-Yang Yu; Hong-Zhong Jin (Journal of Immunology Research)
N6-methyladenosine (m6A) is the most important modification of messenger RNAs (mRNAs) and long noncoding RNAs (lncRNAs) in higher eukaryotes. Modulation of m6A modifications relies on methyltransferases and demethylases. The discovery of binding proteins confirms that the m6A modification has a wide range of biological effects and significance at the molecular, cellular, and physiological levels. In recent years, techniques for investigating m6A modifications of RNA have developed rapidly. This article reviews the biological significance of RNA m6A modifications in the innate immune response, adaptive immune response, and viral infection.